Children in Custody Anglo-Russian Perspectives - McAuley, Mary (Bloomsbury Academic, 2009)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Despite their very different histories, societies, political and legal systems, Russia and the UK stand out as favouring a punitive approach to young law breakers, imprisoning many more children than any other European countries. The book is based on the author's primary research in Russia in which she visited a dozen closed institutions from St Petersburg to Krasnoyarsk and on similar research in England and Northern Ireland. The result is a unique study of how attitudes to youth crime and criminal justice, the political environment and the relationship between state and society have interacted to influence the treatment of young offenders. McAuley's account of the twists and turns in policy towards youth illuminate the extraordinary history of Russia in the twentieth century and the making of social policy in Russia today. It is also the first study to compare the UK (excluding Scotland because of its separate juvenile justice system) with Russia, a comparison which highlights the factors responsible for the making of 'punitive' policy in the two societies. McAuley places the Russian and UK policies in a European context, aiming to reveal how other European countries manage to put so many fewer children behind bars.